Tradisi Ratik Tolak Bala dan Ketahanan Pangan Masyarakat Koto Gadang VI Koto - Septriani, Septriani; Gani, Maulid Hariri; Aziz, Basyarul; Arianto, Tomi (Aceh Anthropological Journal, 2025)
The food security of the Koto Gadang VI Koto community in Agam Regency, West Sumatra, is frequently threatened by crop failures caused by pests such as rats and planthoppers. This study aims to describe how the ratik tolak bala tradition functions as a cultural strategy for maintaining local food security. Employing a qualitative descriptive-analytical approach, the research collected data through participant observation, in-depth interviews with traditional and religious leaders, farmers, and field documentation. Data analysis used the interactive model of Miles and Huberman (reduction, display, conclusion drawing) and was interpreted through C.A. Van Peursen’s framework of tradition (mystical, ontological, and functional stages). The findings reveal that ratik tolak bala originated as a communal response to pest attacks threatening rice crops—the main food source. The ritual consists of two stages: ratik duduak (collective chanting in the mosque) and ratik tagak (processional chanting around the village), accompanied by the application of paureh, a herbal mixture of local plants, and field sanitation activities. Led by a mursyid (religious teacher), the ritual effectively reduced pest infestations, restored harvest yields, and ensured stable household rice stocks. Theoretically, the practice reflects a transition from mystical belief to functional rationality consistent with FAO’s four food security pillars: availability, access, utilization, and stability. Abstrak: Ketahanan pangan masyarakat Nagari Koto Gadang VI Koto di Kabupaten Agam, Sumatera Barat, kerap terancam akibat gagal panen yang disebabkan oleh serangan hama seperti tikus dan wereng. Penelitian ini bertujuan menjelaskan bagaimana tradisi ratik tolak bala berfungsi sebagai strategi budaya masyarakat dalam menjaga ketahanan pangan lokal. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif analitis. Data dikumpulkan melalui observasi partisipan, wawancara mendalam dengan tokoh adat, tokoh agama, petani, serta dokumentasi lapangan. Analisis data dilakukan menggunakan model interaktif Miles dan Huberman yang meliputi reduksi, penyajian, dan penarikan kesimpulan, serta ditafsirkan melalui kerangka teori C.A. Van Peursen (mistis, ontologis, dan fungsional). Hasil penelitian menunjukkan bahwa ratik tolak bala berawal dari upaya masyarakat menghadapi serangan hama yang mengancam sumber pangan. Tradisi ini dilaksanakan melalui dua tahapan utama, yaitu ratik duduak (dzikir di masjid) dan ratik tagak (dzikir keliling kampung), diikuti dengan penggunaan ramuan paureh dari dedaunan lokal dan pembersihan lahan pertanian. Pelaksanaan ritual yang dipimpin mursyid ini terbukti mampu menekan serangan hama, memulihkan hasil panen, dan menjaga keberlanjutan stok pangan rumah tangga. Secara teoritis, tradisi ini menunjukkan peralihan dari keyakinan mistis menuju fungsi rasional yang selaras dengan prinsip ketahanan pangan FAO: ketersediaan, akses, pemanfaatan, dan stabilitas.